PERANCANGAN SISTEM INFORMASI INVENTORI BARANG PADA TOKO AURYN COMPUTER KABUPATEN SOLOK SELATAN - Husaini., Ahmad; Irsyadunas, Irsyadunas (STKIP PGRI Sumatera Barat, 2018)
Auryn Computer Store is an effort to sell computers, accessories and office stationery located in Muara Labuh, South Solok Regency, the process of processing data during this time is done manually by employees. System design uses a modeling language using information system analysis (ASI). While the programming language used is Micrososft Visual Studio 2010 by using the Microsoft Access database. Information systems designed using the SDLC (System Development Life Cycle) method. Goods data management is built an inventory information system at Auryn Computer store in South Solok Regency with the aim to facilitate the management of goods sales data, goods purchase reports, inventory calculation and inventory reports, all data has been stored in the database properly, so that inventory information systems this is very effective and efficient for providing information.